2022
DOI: 10.1002/ldr.4247
|View full text |Cite
|
Sign up to set email alerts
|

Water seepage and retention in purple soil bunds on sloping farmland in the Three Gorges Reservoir area, China

Abstract: Soil bunds are a common land reconstruction practice in the Three Gorges Reservoir area of China, and play a key role in runoff regulation and soil conservation on cultivated hillslopes. This study investigated water movement pathways and retaining effects of soil bunds using water transport trajectory observations inferred from field dye tracing experiments. It was found that water infiltration in the bund was characterised by spatial heterogeneity in three dimensions. The stained area ratio (SAR) of the bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…To counteract the decline in soil productivity caused by tillage erosion, farmers often mix weathered parent material into the soil to maintain soil depth, leading to an increase in the rock fragment in purple soil [9]. Studies have shown that purple soil in the Three Gorges Reservoir area exhibits shallow soil and gravelization characteristics, with gravel contents ranging from 14.2 to 34.4% for particles of 1-3 mm and 51.2 to 74.1% for particles larger than 3 mm [10,11]. It is evident that thin soil layers and high gravel contents are essential characteristics of purple soil.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the decline in soil productivity caused by tillage erosion, farmers often mix weathered parent material into the soil to maintain soil depth, leading to an increase in the rock fragment in purple soil [9]. Studies have shown that purple soil in the Three Gorges Reservoir area exhibits shallow soil and gravelization characteristics, with gravel contents ranging from 14.2 to 34.4% for particles of 1-3 mm and 51.2 to 74.1% for particles larger than 3 mm [10,11]. It is evident that thin soil layers and high gravel contents are essential characteristics of purple soil.…”
Section: Introductionmentioning
confidence: 99%